Ethnobotany of Elaeis guineensis Jacq. and its importance in the household economy of the Ikale and Ilaje of Ondo State, Nigeria - Erinoso, Sakiru Morenikeji; Aworinde, David Olaniran; Teniola, Olasimbo Anuoluwapo; Ojo, Samuel Omoniyi (Ethnobotany Research and Applications, 2020)
Background: African oil palm (Elaeis guineensis Jacq.), a perennial crop that originated from Tropical rainforest of West Africa, is one of the most important economic oil crops in Nigeria providing income for rural and semi-urban folks. This study described the ethnobotany of the plant and evaluated the extent to which it contributes to the livelihood strategies of the Ikale and Ilaje speaking people of Ondo State, Nigeria. Methods: Interviews were conducted in the local language and questionnaires were administered to willing respondents. Photographs of tools/machines used in the production of palm oil and allied products were taken. Drawings of the tools were generated on site. Results: The plant is the principal source of palm oil. Major processing tools of palm oil include cracker, presser, digester, and boiling trough. Other products that are derived from oil palm parts are palm kernel oil, kernel meat (for livestock feed), kernel shells (for fuel), palm wine, broom, fish trap, and traditional soap. All these products are made using indigenous methods. They feature in medicinal preparations, traditional ceremonies and are important household commodities. Conclusions: The products derived from oil palm tree serve as means of livelihood in the study communities and are local resources used in everyday activities of the people. The indigenous production methods observed further emphasize the role these products play in the economy of oil palm product makers and sellers. Sustainable tapping of palm wine should be encouraged in order to derive maximum benefits from oil palm tree. Keywords: Ethnobotany, Economic Botany, African Oil Palm, Ondo State, Nigeria